Epworth sleepiness scale is associated with hypothyroidism in male patients with obstructive sleep apnea - Wang, Le; Fang, Xiaoyan; Xu, Chong; Pan, Na; Wang, Yan; Xue, Tuai; Zhang, Mingchu; Cao, Jie; Zhang, Jing (Frontiers in Endocrinology, 2022)
Background: Hypothyroidism could cause obstructive sleep apnea (OSA), however, the specific association of them remained unclear. This cross-sectional study aimed to determine the prevalence of hypothyroidism among patients with OSA, and the characteristics and predictors of hypothyroidism associated with OSA. Methods: A total of 573 patients with OSA were included in the study. Serum levels of thyroid stimulating hormone (TSH), free trriodothyronine (FT3) and free thyroxine (FT4) were measured in all participants. Univariate and binary logistic regression analysis were performed to assess the association of OSA with hypothyroidism while controlling for potential confounders. Receiver operating characteristic (ROC) curve analysis was performed to evaluate the OSA effect in the distinction between euthyroid and hypothyroidism. Results: The prevalence of hypothyroidism was 6.75%、5.12%、10.38% in the total, men, and women cohort, respectively, and the prevalence rate in women OSA patients was significantly higher than that in men OSA patients (P=0.018). The men OSA patients with hypothyroidism had a higher Epworth sleepiness scale (ESS) than women OSA patients with hypothyroidism (P=0.022). Additionally, the ESSwas significantly higher in men OSA patients with hypothyroidism than those with euthyroid (P=0.042), while women OSA patients had no such difference (P=0.822). In men patients with OSA, ROC curve analyses revealed that the risk of hypothyroidism increased in accordance with increasing ESS after adjustment for potential confounders, and the optimal cutoff value was 10 score. Higher ESS category was significantly associated with a higher risk of prevalent hypothyroidism in men patients with OSA [odds ratio (OR) = 4.898 for ESS≥10 relative to ESS <10, 95% confidence interval (CI) 1.628-14.731, P = 0.005]. Conclusions: The prevalence of hypothyroidism in OSA patients was relatively higher, especially in women OSA patients. ESS was significantly and positively associated with hypothyroidism in men patients with OSA, suggesting that ESS may have a potential role in identification and diagnosis of men OSA patients complicated with hypothyroidism.